2015
DOI: 10.1371/journal.pone.0116560
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Diesel Exhaust Particle Extracts (DEPe) Impairs Some Polarization Markers and Functions of Human Macrophages through Activation of AhR and Nrf2

Abstract: Macrophages (MΦ), well-known to play an important role in immune response, also respond to environmental toxic chemicals such as diesel exhaust particles (DEP). Potential effects of DEPs towards MΦ polarization, a key hall-mark of MΦ physiology, remain however poorly documented. This study was therefore designed to evaluate the effects of a reference DEP extract (DEPe) on human MΦ polarization. Human blood monocytes-derived MΦ were incubated with IFNγ+LPS or IL-4 to obtain M1 and M2 subtypes, respectively; a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 70 publications
3
31
0
Order By: Relevance
“…The aryl hydrocarbon receptor (AhR) is a key transcription factor involved in pulmonary immune responses to urban combustion products, including diesel exhaust and tobacco smoke (19, 30, 31). To investigate whether different types of animal dung biomass smoke contain ligands of the AhR, we used a well-characterized AhR activity assay utilizing mouse liver cells with a luciferase reporter (23, 25, 32, 33).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aryl hydrocarbon receptor (AhR) is a key transcription factor involved in pulmonary immune responses to urban combustion products, including diesel exhaust and tobacco smoke (19, 30, 31). To investigate whether different types of animal dung biomass smoke contain ligands of the AhR, we used a well-characterized AhR activity assay utilizing mouse liver cells with a luciferase reporter (23, 25, 32, 33).…”
Section: Resultsmentioning
confidence: 99%
“…Important regulators of airway inflammatory responses to inhaled pollutants that we assessed with dung biomass smoke exposure were the AhR and AP-1 (19, 30, 31). Similar to previous work examining the effects of dung smoke by us and others, we found that six different types of dung biomass smoke can activate the AhR (Figure 5) and AP-1 (Figure 6) in human airway epithelial cells (6, 8).…”
Section: Discussionmentioning
confidence: 99%
“…Although cigarette smoke shares similar characteristics to particulate pollution, exposure to cigarette smoke has been shown to skew macrophages towards an M2 phenotype 44. Treatment of polarised human monocyte derived M1 and M2 macrophages with diesel exhaust particles impairs expression of some M1 and M2 markers without overall inhibition of the polarisation process while increasing secretion of the M1 and M2 cytokines IL-8 and IL-10, respectively, via activation of Ahr and Nrf2 91. Although lung macrophages orchestrate the inflammatory responses induced by exposure to air pollutants resulting in adverse lung and cardiovascular effects, it remains to be determined which factors such as size and composition of particulate matter determine macrophage polarisation.…”
Section: The Environment and Agingmentioning
confidence: 99%
“…Increased levels of the HbA protein were also observed in the hippocampi of subjects in the DEP group. A recent report indicated that DEP extract can activate Nrf2 and aryl hydrocarbon receptor (AhR) pathways in vitro (Jaguin et al, 2015). Thus, nanoparticles such as DEP induce oxidative or inflammatory stress, which likely results in Nrf2 activation in the fetal/neonatal brain.…”
Section: Discussionmentioning
confidence: 99%